Control of a photovoltaic system by fuzzy logic, comparative studies with conventional controls: results, improvements and perspectives. (2017) - Issaadi, Wassila
This study presents the principle of the MPPT command. The command techniques most used in MPPT control are reviewed and analysed such as: observation and perturbation (O&P) and conductance incrementing (CI). The aim of this study is the association of the fuzzy logic command with the MPPT command, then analysing and comparing its behaviour with other techniques (O&P and CI) used in the control of photovoltaic systems.